Analysis of the modern functional field of effective implementation of public control in the system of public administration in Ukraine - Pukhkal, Oleksandr; Reiterovych, Ihor; Kuprii, Tetiana; Sytnyk, Svitlana; Novikov, Oleksiy (P.A. Persona e Amministrazione, 2023)
The development of technologies and globalisation has necessitated the analysis of the modern functional field of effective public control in the system of public administration in Ukraine. In modern Ukrainian society there is a clear demand for effective ways to involve the general public and create real mechanisms for implementing democratic principles of public administration through European integration processes, cleansing the public administration system of corruption, eliminating the shadow scheme of public administration decisions in narrow corporate interests. Thus, the study of the public administration system in Ukraine is an important and relevant issue. The aim of the study is to analyse the current functional field in the processes of public control in the public administration system of Ukraine. The following research methods were used: analysis and synthesis of information, comparative method, method of sociological research, as well as the method of induction. At the final stage of the study, an analysis of scientific sources on the research topic was carried out. According to the results of the study, it can be argued that the effectiveness of public control in Ukraine directly depends on the state of development of civil society and the level of interaction of its subjects with state authorities and their officials. This largely depends on the motivation of the competent authorities, since state institutions, especially in the legal and organisational spheres, ensure the development of civil society and form the basis for public participation in governance. The practical significance of the research results lies in the fact that the research presented in the article and the analysis of literature sources provides an idea of the implementation of public control in the public administration system in Ukraine, and also opens up new opportunities for its improvement.